2004
DOI: 10.1111/j.1475-1313.2004.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

A 6‐month follow‐up of successful refits from daily disposable soft contact lenses to continuous wear of high‐Dk silicone‐hydrogel lenses

Abstract: The present studies confirm that the continuous wear of SiH lenses for up to 30 days can be considered as an alternative to daily disposable soft lens wear, but is not suitable for everyone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…After a large-scale clinical study, Brennan et al 28 reported 0.1% incidence of neovascularization in high Dk silicone hydrogel wearers. After 6 months, Aakre et al 37 reported statistically lower levels of neovascularization in silicone hydrogel wearers compared with low Dk daily disposables wearers. In addition, 5 of their 16 (31%) daily lens wearers compared with 1 out of the 30 (3%) silicone hydrogel lens wearers demonstrated grade 1 or greater (deemed clinically significant) neovascularization at 6 months.…”
Section: Neovascularizationmentioning
confidence: 99%
“…After a large-scale clinical study, Brennan et al 28 reported 0.1% incidence of neovascularization in high Dk silicone hydrogel wearers. After 6 months, Aakre et al 37 reported statistically lower levels of neovascularization in silicone hydrogel wearers compared with low Dk daily disposables wearers. In addition, 5 of their 16 (31%) daily lens wearers compared with 1 out of the 30 (3%) silicone hydrogel lens wearers demonstrated grade 1 or greater (deemed clinically significant) neovascularization at 6 months.…”
Section: Neovascularizationmentioning
confidence: 99%
“…5,6 Dryness problems vary according to lens material and lens care system, and several studies have suggested that they are reduced with silicone hydrogel lens wear. [7][8][9] Corneal fluorescein staining can be indicative of a wide range of problems in contact lens wearers, including reactions to lens care solutions, lens desiccation, and mechanical disruption. Corneal staining is frequently seen in nonwearers and contact lens wearers and, depending on the severity, may not necessarily require remedial action.…”
mentioning
confidence: 99%
“…Arguably the most common complaint in contact lens wearers is that of dry eye symptoms, 5 now more commonly referred to as CLIDE, 4 there is evidence of bulbar conjunctiva staining (perhaps in a 3 and 9 pattern) and some degree of hyperemia. 7 Logically, the detection and monitoring of the extent of these cellular changes underlying the symptoms and staining should be performed with CIC at the nasal or temporal location within the habitual palpebral aperture (i.e., what some might refer to as the interpalpebral bulbar conjunctiva). However, if the patient's main problem were with SEALs, then it would be more logical to target the superior bulbar conjunctiva.…”
Section: Concluding Remarks and Directions For Future Studiesmentioning
confidence: 99%
“…4 Any abnormality in the tear film will likely lead to alterations in the health of the bulbar conjunctiva (and the epithelium covering the corneal surface) and result in the development of symptoms. [5][6][7][8] Based on the clinical observations of established contact lens wearers, any such desiccation-related effects are more likely to be localized at least as viewed by slitlamp biomicroscopy. Perhaps the best well-known localized change is that of Ô3 and 9 staining,Õ visualized after the instillation of fluorescein and usually seen as a broad line extending across the mid-to-inferior cornea and over onto the specified clock positions close to the horizontal meridian of the habitual palpebral aperture.…”
mentioning
confidence: 99%